Primary Non-Hodgkin’s Lymphoma of the bilateral Breast and review the literature - Makhubele, Hundzukani Dost; Bhuiyan, Mirza MZU (Jour Med Resh and Health Sci, 2020)
Primary bilateral breast Non-Hodgkin’s lymphomas are the rare tumors found during the pregnancy and postpartum period. Diffuse large B-cell lymphoma (DLBCL) is the most common histological diagnosis. Lymphomas in breasts grow faster in pregnant or postpartum women especially, in those who are infected with Human Immunodeficiency Virus (HIV). Confirmation of diagnosis is usually delayed because of breasts’ extraordinary engorgement, hormonal changes during the pregnancy or lactation and most of the patients are diagnosed in advanced stages. Rapidly growing breast mass in HIV patients during the antenatal and postpartum period should undergo prompt investigations and early treatment if proven lymphoma.